2005
DOI: 10.1128/jvi.79.15.9381-9387.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Secret Agent as the O- GlcNAc Transferase That Participates in Plum Pox Virus Infection

Abstract: Serine and threonine of many nuclear and cytoplasmic proteins are posttranslationally modified with O-linked N-acetylglucosamine (O-GlcNAc). This modification is made by O-linked N-acetylglucosamine transferases (OGTs). Genetic and biochemical data have demonstrated the existence of two OGTs of Arabidopsis thaliana, SECRET AGENT (SEC) and SPINDLY (SPY), with at least partly overlapping functions, but there is little information on their target proteins. The N terminus of the capsid protein (CP) of Plum pox vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…On one hand, CP is phosphorylated by the protein kinase CK2, a modification that seems to regulate the RNA binding function of CP and therefore likely controls the formation and/or stability of viral ribonucleoproteins (59)(60)(61). On the other hand, O-GlcNAcylation modifications carried out by the host protein SECRET AGENT were also found in PPV CP (59,62). Interestingly, a mutagenic approach showed that O-GlcNAcylation might have a role in virion assembly and/or stability (63).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, CP is phosphorylated by the protein kinase CK2, a modification that seems to regulate the RNA binding function of CP and therefore likely controls the formation and/or stability of viral ribonucleoproteins (59)(60)(61). On the other hand, O-GlcNAcylation modifications carried out by the host protein SECRET AGENT were also found in PPV CP (59,62). Interestingly, a mutagenic approach showed that O-GlcNAcylation might have a role in virion assembly and/or stability (63).…”
Section: Discussionmentioning
confidence: 99%
“…This fact is inconsistent with variable CP mobility in SDS-PAGE, which is apparently caused by non-amino acid compounds coupled with CP molecules by posttranslational modification (Šubr and Glasa, 2004;Kollerová et al, 2008). O-glycosylation of CP serine and threonine residues by N-acetylglycosamine has been detected and the corresponding plant enzyme was identified (Fernández-Fernández et al, 2002;Chen et al, 2005;Scott et al, 2006). Localization of this modification in the N-terminal CP part is in agreement with the fact that core CP of different PPV strains migrated equally in SDS-PAGE Šubr and Glasa, 1999).…”
Section: Capsid Proteinmentioning
confidence: 93%
“…Two OGT proteins have been identiWed in Arabidopsis-SPY and SECRET AGENT (SEC)-the latter being more closely related to human OGT (Hartweck et al 2002). It has been demonstrated that SEC is involved in the O-GlcNAc modiWcation of the Nterminus of a capsid protein of the plum pox virus (Chen et al 2005). However, to date, no proteins modiWed by SPY have been reported.…”
Section: Introductionmentioning
confidence: 99%